Analysis on artist neuropsychology and art creation - Huang Yaqi (De Gruyter, 2019)
Based on Carl Gustav Jung’s persona philosophy, this paper conducts theoretical analysis on the introvert and extravert personalities, distinguishes the introvert personality from the psychopathy defined from a medical perspective, and elaborates on the dominance of introvert personality in art creations, as well as the “mental conditions” among artists that the contemporary society is concerned with. This paper uses modern artists as subjects to support the conclusion through analysis of their childhood, career and life stories.